Decentralized Solar Photovoltaic Distributed Generation Integrated with Blockchain Technology: A Case Study in Lagos - Oyekola, Abigail (Auckland University of Technology, 2020)
The energy industry is moving from the standard distribution energy grid to decentralised renewable energy distributed generation networks. Solar photovoltaic energy is an example of the latter method used to integrate renewable energy sources into the energy industry. However, the impact of this decentralised model as the primary source of energy generation on the centralised grid and the energy industry, is uncertain. Therefore, this research investigates the possibility of renewable energy sources as the primary source of energy generation in the Nigerian energy system; and explores energy trading through the secured blockchain energy-trading platform used by Nigerians. This was achieved by modelling and simulating a decentralised distributed solar photovoltaic generation network in the Lagos State of Nigeria that adopts blockchain technology as the energy-trading platform MATLAB/Simulink software was used to model and simulate a section of the Nigerian energy network, where solar photovoltaic distributed generation systems were installed in decentralised locations. Subsequently, Python was used to create an algorithm illustrating how the secured blockchain energy-trading platform should function. Then, RETScreen Expert software was used to carry out the financial sensitivity and risk analyses of implementing this project in the Nigerian energy industry. Research demonstrated that implementing a decentralised distributed solar photovoltaic generation network into the Nigeria energy system could improve the reliability and efficiency of energy generation and supply during different seasons of the year. This was dependent on the appropriate design of the solar photovoltaic generation system and the central storage system. It was also found that the blockchain energy-trading platform could serve as a source of income for some people. This could encourage more Nigerians to efficiently use their generated energy so that enough can be sold to other energy consumers.
Keywords: Solar photovoltaic energy generation; Decentralised distributed generation system; Blockchain technology energy trading platform; Financial, sensitivity and risk analysis